Spectrophotometric determination of hydrochlorothiazide using charge transfer interactions with alizarin red s reagent - Ikhlass Thanone Al-Allaf; Nabeel Sabeeh Othman; Amer Thanoon Al-Taee (African Journal of Advanced Pure and Applied Sciences, 2023)
The present work included using transferred charge complex reaction in the assay of Hydrochlorothiazide using Alizarin Red S as an electron acceptor. The method is based on direct spectrophotometric estimation of hydrochlorothiazide by its reaction with Alizarin Red –S in absolute methanol media through forming a red charge transfer complex solution that gives a maximum absorption at 537 nm. The relation between concentration and absorbance was linear within the concentration range of 0.1-2.5 μg / ml with the molar absorption coefficient equal to 1.2774 × 105 l. mol-1. cm-1. The method was successfully applied to estimate hydrochlorothiazide in its pharmaceutical preparations (tablets).